Effect of water content on the resilient behavior of non standard unbound granular materials. (June 2016) - Coronado, Octavio; Caicedo, Bernardo; Taibi, Said; Gomes Correia, Antonio; Souli, Hanène; Fleureau, Jean-Marie
Abstract: The results of an experimental study on non-standard road granular materials are presented, including small strain precision triaxial tests under cyclic loading and wetting tests. The materials have attrition coefficients, plasticity index, and fines content above the recommended limits. The influence of each parameter and the influence of the water content were studied. This work emphasizes the role of suction in the interpretation of the results, and the possibility to use an effective stress approach to express the changes in normalized resilient modulus as a function of a single parameter representing both total stresses and suction. Among the three effective stress definitions tested, those of Terzaghi and Taibi were shown to yield satisfactory results. This approach noticeably simplifies the characterization of UGM specimens at different water contents in the perspective of a more rational design of pavement layers.